1987
DOI: 10.1111/j.1476-5381.1987.tb11374.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐related effects of pharmacological mediators on tracheal vascular resistance in dogs

Abstract: IVarious doses of mediators were tested on tracheal vascular resistance in dogs anaesthetized with pentobarbitone. Tracheal vascular resistance was determined by perfusing the cranial tracheal arteries at constant flows and measuring inflow pressures. 2 All drugs produced dose-related changes in vascular resistance. 3 The peptides bradykinin, substance P and vasoactive intestinal peptide (VIP) each had similar vasodilator potencies and were much more powerful than histamine, methacholine and salbutamol.4 Plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
2
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 13 publications
5
24
2
1
Order By: Relevance
“…In another study fatal asthma was characterized by an increase in both numbers of large vessels and total vessel area in the cartilaginous airways, suggesting enlargement of existing vessels [6]. The authors have not assessed large airway vessel size and area, because such measurements may be artificially distorted by tangential cutting of vessels and vasodilatation induced by b 2 -agonists [19] or vasoactive mediators [20]. Furthermore, results from animal studies have shown that most of the airway narrowing is due to extravasation of plasma fluid rather than vascular congestion [21].…”
Section: Discussionmentioning
confidence: 99%
“…In another study fatal asthma was characterized by an increase in both numbers of large vessels and total vessel area in the cartilaginous airways, suggesting enlargement of existing vessels [6]. The authors have not assessed large airway vessel size and area, because such measurements may be artificially distorted by tangential cutting of vessels and vasodilatation induced by b 2 -agonists [19] or vasoactive mediators [20]. Furthermore, results from animal studies have shown that most of the airway narrowing is due to extravasation of plasma fluid rather than vascular congestion [21].…”
Section: Discussionmentioning
confidence: 99%
“…These include histamine, methacholine, 5-HT, peptides and prostaglandins (Laitinen et al, 1987;Salonen et al, 1988;Corfield et al, 1991). Here PAF has been shown to be one of the most potent vasodilators yet studied in this system, second only to the other inflammatory mediator bradykinin which is also notable for its extremely long duration of action (Corfield et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The tracheobronchial circulation will have an important role in modulating these actions. However, the actions of PAF on airways blood flow has been little studied (Laitinen et al, 1987) and its mode of action is unknown. PAF induces microvascular leakage in the airways which may be due to a direct rather than indirect action on the vasculature since in guinea-pigs it is independent of cyclo-oxygenase or lipoxygenase products (Evans et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, stimulation of the central end of a vagus nerve causes tracheal vasoconstriction, systemic hypertension and smooth muscle contraction via impulses came from the cardiac nerves not the pulmonary or abdominal branches of the vagus (Ş ahin et al 1987a). Whether or not parasympathetic cholinergic fibers to the laryngeal vasculature can cause relaxation is more controversial, and in general histological studies do not support a close cholinergic innervation of the vessels (Laitinen et al 1987b). Furthermore, the exact motor pathways have not been identified.…”
Section: Yelmen Nk şAhin G and Oruç T The Effects Of Vagal Stmentioning
confidence: 99%
“…Although the role of parasympathetic and sympathetic nerves to the laryngeal vascular bed are not well established, the stimulation of superior laryngeal nerve causes nasal and tracheal vasodilatation (Laitinen et al 1987a;Dylewska et al 1993). This response can be blocked by muscarinic agents such as atropine and may be caused by acetylcholine and metacholine (Laitinen et al 1987b). On the other hand, Laitinen et al (1987a) suggested that vasodilatation caused by parasympathetic nerve stimulation in nose and trachea after atropine administration, may be mediated by the release of neuropeptides such as VIP.…”
Section: Yelmen Nk şAhin G and Oruç T The Effects Of Vagal Stmentioning
confidence: 99%